The Use of KORSIMU to Enhance Breast Milk Production - Mufdlilah (International Journal of Psychosocial Rehabilitation, 2020)
— This research aims to increase the production of breast milk by breastfeeding mothers through the development of a chair device known as KORSIMU. This is an R&D research consisting of two phases. The result showed that in the first phase, six mothers stated that KORSIMU was comfortable to use, and the incorporated massage facilities, helped to stimulate the oxytocin hormone. In the second phase, a trial was carried out on six breastfeeding mothers, and four felt the breast milk flow smoothly after using the device. Therefore, it is necessary to develop the oxytocin massage part of the device in the fifth and sixth costae and to add foams in the chair to make it more comfortable.